2022
DOI: 10.1371/journal.pone.0272208
|View full text |Cite
|
Sign up to set email alerts
|

A cross-country analysis of macroeconomic responses to COVID-19 pandemic using Twitter sentiments

Abstract: The COVID-19 pandemic has had a devastating impact on the global economy. In this paper, we use the Phillips curve to compare and analyze the macroeconomics of three different countries with distinct income levels, namely, lower-middle (Nigeria), upper-middle (South Africa), and high (Canada) income. We aim to (1) find macroeconomic changes in the three countries during the pandemic compared to pre-pandemic time, (2) compare the countries in terms of response to the COVID-19 economic crisis, and (3) compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
1
8
0
1
Order By: Relevance
“…If the points are mainly sloping upwards, it indicates a positive relationship, while a downward slope indicates a negative relationship which is our case. This finding is consistent with Nia et al's (2022) study in Canada, which revealed that although unemployment rates were controlled and reduced during the pandemic, inflation surged to unprecedented levels, a trend also observed in the United States.…”
Section: Discussion and Suggestionssupporting
confidence: 91%
“…If the points are mainly sloping upwards, it indicates a positive relationship, while a downward slope indicates a negative relationship which is our case. This finding is consistent with Nia et al's (2022) study in Canada, which revealed that although unemployment rates were controlled and reduced during the pandemic, inflation surged to unprecedented levels, a trend also observed in the United States.…”
Section: Discussion and Suggestionssupporting
confidence: 91%
“…Conversely, sentiment from non-news accounts does not exhibit a significant relationship with GDP. This finding introduces a novel perspective and evidence compared to studies by Abbas et al (2022), Jabeen et al (2022), and Nia et al (2022, suggesting that a positive relationship between Twitter sentiment and GDP is more likely when sentiment from news accounts is predominant. These findings underscore the pivotal role of social media, particularly Twitter, as a platform for capturing public opinion that can be linked to macroeconomic indicators.…”
Section: Resultsmentioning
confidence: 62%
“…To combat the COVID-19 pandemic, governments and private companies around the world were promoting the use of digital public health technologies for data collection and processing [54][55][56][57][58]. Through the use of GPS, cellular networks and Wi-Fi, smartphones can collect and aggregate location data in real-time to monitor population flows, identify transmission hotspots, determine the effectiveness of non-pharmacologic interventions [59], and predict future COVID-19 cases [7,20,25].…”
Section: Discussionmentioning
confidence: 99%